Polyamide-imide resin, resin composition, and semiconductor device
Patent Information
- Application Number
- JP2024192033
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-03-04
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2042-01-12
AI Technical Summary
【0021】 本発明によれば、耐熱性に優れ、部材間の密着性を高めて高温での剥離の発生を抑制することができ、半導体装置において部材間のプライマー層形成材料として好適に使用できる、樹脂材料を提供することができる。
Smart Images

Figure 2025023975000001_ABST
Abstract
Description
[Technical field]
[0001] The present embodiment relates to a polyamide-imide resin containing a cardo-type fluorene skeleton, a resin composition containing the polyamide-imide resin, and a semiconductor device using the resin composition. [Background technology]
[0002] Carbon dioxide (CO2) emitted from various industrial equipment is one of the main causes of global warming. Therefore, there is a demand for the creation of a low-carbon society in order to solve the global warming problem. One method for realizing a low-carbon society is to apply power semiconductors to industrial equipment to reduce power loss. Power semiconductors are also used in various applications such as automobiles, and the demand for them is increasing. Examples of power semiconductors for automobiles include power cards, as well as TO, SOP, QFP, BGA, and CSP packages.
[0003] In recent years, especially with the electrification of automobiles (EVs), the power density of power semiconductors has improved and the operating temperature (Tj) of devices has risen. As a result, the temperature required for heat cycle testing has also risen. However, in conventional power semiconductors, peeling may occur between components, such as the interface between the resin sealing layer and the substrate or the semiconductor element, during a heat cycle test assuming a higher operating temperature (higher Tj). Peeling between components in a semiconductor device may lead to failure, resulting in a significant decrease in the reliability of the semiconductor device.
[0004] In order to meet the demand for high Tj of power semiconductor devices, various studies have been conducted from the viewpoint of the resin encapsulation material constituting the resin encapsulation layer. For example, development of resin encapsulation materials with excellent heat resistance has been promoted, and resin encapsulation materials with glass transition temperatures exceeding 230°C exhibit excellent heat resistance even in high temperature ranges exceeding 200°C. However, on the other hand, as the resin hardens, the adhesion with the components decreases, and the reliability of the semiconductor device is likely to decrease. In addition, peeling may occur between the components during the reflow process when mounting the device. Therefore, from the viewpoint of improving the reliability of semiconductor devices, a method for improving adhesion between components in a semiconductor device is desired in order to suppress peeling between the components during high-temperature heat cycle tests and reflow processes.
[0005] In response to this, a method is known in which a primer layer made of a resin material is formed between components of a semiconductor device to improve adhesion between the components and thereby prevent peeling. For example, a method is being considered in which a primer layer made of a polyamideimide resin is provided between a metal lead frame and a sealing material to suppress the occurrence of peeling (Patent Document 1). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2013-135061 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, as the Tj of power semiconductor devices increases, the conditions required for reliability tests of the semiconductor devices become stricter, and it is difficult for conventional resin materials to fully satisfy the required conditions. Therefore, from the viewpoint of providing highly reliable power semiconductors, there is a continuing need for development of resin materials with excellent heat resistance that can prevent peeling between components even in high-temperature regions exceeding 250°C, for example.
[0008] Therefore, in view of the above-mentioned circumstances, the present invention provides a resin material that has excellent heat resistance, can improve adhesion between components, and can suppress the occurrence of peeling, and can be particularly suitably used as a primer layer forming material provided between components of a semiconductor device. [Means for solving the problem]
[0009] From the viewpoint of improving the peeling between components in the heat cycle test in the high temperature range, it is preferable that the resin material forming the primer layer has a glass transition temperature (Tg) higher than the upper limit of the driving temperature (Tj) of the power semiconductor. It is generally known that a resin softens at a temperature exceeding the Tg of the resin, and the adhesion decreases. Therefore, if the Tg of the resin is lower than the driving temperature of the power semiconductor, the heat resistance becomes insufficient, and it becomes difficult to ensure the adhesion between the components. As a result, for example, peeling occurs between the resin sealing layer and the substrate or the semiconductor element.
[0010] The inventors have conducted extensive research into polyamide-imide resins and their resin compositions as resin materials, and have found that polyamide-imide resins having a cardo-type fluorene skeleton have a high Tg. In addition, the inventors have found that when a primer layer is formed between each member, such as between a resin sealing layer and a substrate or a semiconductor element, using a polyamide-imide resin having the above-mentioned specific structural unit or a resin composition containing this resin, excellent adhesion between the members can be obtained, and have completed the present invention.
[0011] That is, the embodiments of the present invention relate to the following: However, the present invention is not limited to the following embodiments, and various modifications can be made.
[0012] One embodiment relates to a polyamideimide resin comprising a structural unit (Ia) represented by the following formula and at least one selected from the group consisting of structural units (IIa), (IIb), and (IIc) represented by the following formulas: [ka] [ka]
[0013] In the above formula (Ia), each X independently represents a hydrogen atom or a substituent selected from the group consisting of a halogen atom, an alkyl group having 1 to 9 carbon atoms, an alkoxy group having 1 to 9 carbon atoms, and a hydroxyalkyl group. In the above formulae (IIa), (IIb), and (IIc), each S independently represents an alkyl group having 1 to 3 carbon atoms, a represents an integer of 0 to 4, b represents an integer of 0 to 3, and c represents an integer of 0 to 4.
[0014] The polyamideimide resin preferably further contains a structural unit (IIIa) represented by the following formula: [ka]
[0015] In the above formula (IIIa), R each independently represents a hydrogen atom or a substituent selected from the group consisting of an alkyl group having 1 to 9 carbon atoms, an alkoxy group having 1 to 9 carbon atoms, and a halogen atom, and n represents an integer of 1 to 6.
[0016] The polyamideimide resin preferably has a linear expansion coefficient of 40 to 70 ppm / °C.
[0017] In the polyamideimide resin, the proportion of the structural unit (Ia) is preferably 20 mol % or more based on the total amount of the structural unit (Ia) and at least one selected from the group consisting of the structural units (IIa), (IIb), and (IIc).
[0018] The polyamide-imide resin preferably has a glass transition temperature of 250° C. or higher. The polyamide-imide resin more preferably has a glass transition temperature of 300° C. or higher.
[0019] Another embodiment relates to a polyamideimide resin composition comprising the polyamideimide resin of the above embodiment and a solvent. The polyamideimide resin composition preferably further comprises a coupling agent.
[0020] Another embodiment relates to a semiconductor device including a substrate and a film formed using the polyamideimide resin composition of the above embodiment. The semiconductor device preferably further includes a resin sealing layer. Effect of the Invention
[0021] According to the present invention, it is possible to provide a resin material that has excellent heat resistance, can increase adhesion between components, and can suppress the occurrence of peeling at high temperatures, and can be suitably used as a material for forming a primer layer between components in a semiconductor device. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a semiconductor device according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Preferred embodiments of the present invention will be described in detail below, however, the present invention is not limited to the following embodiments.
[0024] <Polyamide-imide resin> In one embodiment, the polyamideimide resin contains a structural unit (Ia) described below and at least one selected from the group consisting of structural units (IIa), (IIb), and (IIc). Details of each structural unit are as follows.
[0025] The structural unit (Ia) is represented by the following formula: [ka]
[0026] In the structural unit (Ia), X may be the same or different. Each X independently represents a hydrogen atom or a substituent selected from the group consisting of a halogen atom, an alkyl group having 1 to 9 carbon atoms, an alkoxy group having 1 to 9 carbon atoms, and a hydroxyalkyl group. The halogen atom may be a fluorine atom, a chlorine atom, or a bromine atom. The alkyl group and the alkoxy group may have any of a straight chain structure, a branched structure, and a cyclic structure.
[0027] In one embodiment, each X is preferably a hydrogen atom, an alkyl group having 1 to 9 carbon atoms, or a halogen atom. The alkyl group is more preferably an alkyl group having 1 to 6 carbon atoms, and further preferably an alkyl group having 1 to 3 carbon atoms. In one embodiment, each X is preferably a hydrogen atom.
[0028] The structural units (IIa), (IIb), and (IIc) are each represented by the following formula: [ka]
[0029] In the above structural units (IIa), (IIb), and (IIc), each S independently represents an alkyl group having 1 to 3 carbon atoms, a represents an integer of 0 to 4, b represents an integer of 0 to 3, and c represents an integer of 0 to 4. The alkyl group may be either a linear structure or a branched structure, but is preferably a linear structure. The number of carbon atoms in the alkyl group is more preferably 1 or 2. When the alkyl group is a linear structure, particularly when it is an alkyl group having 1 or 2 carbon atoms, it tends to be easy to obtain a resin with a rigid structure. By forming a film using a resin with a rigid structure, it tends to be easy to keep the coefficient of linear expansion (CTE) low. By keeping the CTE of the film low, it becomes easy to keep the CTE difference with other members small, for example, in the use environment of a semiconductor device. As a result, for example, in a semiconductor device, the stress generated by heat can be reduced, and the reliability of the semiconductor device tends to be easily improved.
[0030] In one embodiment, the structural units (IIa), (IIb), or (IIc) can be derived using a diamine compound or a diisocyanate compound having a structure corresponding thereto. Specific examples of diamine compounds from which the structural units (IIa), (IIb), and (IIc) can be derived include, but are not limited to, the following. The amino group shown in the following compounds may be substituted with an isocyanate group. [ka]
[0031] [ka]
[0032] [ka]
[0033] In one embodiment, a in the structural unit (IIa) is preferably 0 to 3, more preferably 0 to 2, even more preferably 0 or 1, and most preferably 0. b in the structural unit (IIb) is preferably 0 to 2, more preferably 0 or 1, and most preferably 0. c in the structural unit (IIc) is preferably 0 to 3, more preferably 0 to 2, even more preferably 0 or 1, and most preferably 0. When the number of substituents in the structural unit (IIa), (IIb), or (IIc) is smaller, particularly when it is unsubstituted (i.e., when a, b, or c is 0), it tends to be easier to obtain a resin with a rigid structure. By forming a film using a resin with a rigid structure, it tends to be easier to keep the linear expansion coefficient (CTE) low. By keeping the CTE of the film low, it becomes easier to keep the CTE difference with other members small, for example, in the use environment of a semiconductor device. As a result, for example, in a semiconductor device, the stress generated by heat can be reduced, and the reliability of the semiconductor device tends to be easily improved.
[0034] From the above viewpoint, in one embodiment, the polyamideimide resin preferably contains the structural unit (Ia) and at least one selected from the group consisting of the structural units (IIa-1), (IIb-1), and (IIc-1) represented by the following formula: Although not particularly limited, a structure in which two bonding sites (represented by "*") with other structural sites are in a para-position relationship with each other is more preferable.
[0035] [ka]
[0036] A polyamide-imide resin is a resin having an amide bond and an imide bond in the molecular skeleton, and is obtained, for example, by the reaction of a diamine component or a diisocyanate component with an acid component such as a tricarboxylic acid anhydride. From this viewpoint, in one embodiment, a polyamide-imide resin containing the structural unit (Ia) and at least one of the structural units (IIa), (IIb), and (IIc) can be derived using a compound represented by the following formula (I) and at least one compound represented by the following formulas (IIA), (IIB), and (IIC). The structural unit (Ia) and the structural units (IIa), (IIb), and (IIc) correspond to the residues obtained by removing the substituent Y (amino group or isocyanate group) from the compounds represented by the following formulas (I), (IIA), (IIB), and (IIC), respectively, and may be directly bonded to the amide bond site or the imide bond site in the resin structure.
[0037] [ka]
[0038] In the above formula (I), Y is an amino group (-NH2) or an isocyanate group (-NCO), and X is as explained above in the section (Ia).
[0039] [ka]
[0040] In the above formulas (IIA), (IIB), and (IIC), Y is an amino group (-NH2) or an isocyanate group (-NCO), and S, a, b, and c are as described above.
[0041] Specific examples of the compound represented by the above formula (I) include 9,9-bis(4-aminophenyl)fluorene, 9,9-bis(4-amino-3-methylphenyl)fluorene, 9,9-bis(4-amino-3-chlorophenyl)fluorene, and 9,9-bis(4-amino-3-fluorophenyl)fluorene, etc. These can be suitably used as diamine compounds capable of deriving the structural unit (Ia).
[0042] Specific examples of the compound represented by the above formula (IIA) include 4,4'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, and 3,3'-diaminodiphenylmethane, which can be suitably used as a diamine compound capable of deriving the structural unit (IIa-1).
[0043] Specific examples of the compound represented by the formula (IIB) include 1,5-naphthalenediamine and 1,8-naphthalenediamine, which can be suitably used as diamine compounds capable of deriving the structural unit (IIb-1).
[0044] Specific examples of the compound represented by the above formula (IIC) include 1,3-phenylenediamine and 1,4-phenylenediamine, which can be suitably used as diamine compounds capable of deriving the structural unit (IIc-1).
[0045] From the viewpoint of suppressing peeling between components at the driving temperature (Tj) or reflow temperature of the power semiconductor, the polyamide-imide resin preferably has a glass transition temperature higher than the upper limit of Tj or the reflow temperature. In this specification, the "glass transition temperature (Tg)" is a value obtained by using a thermomechanical analyzer and using a film obtained by applying and heating and drying a resin dissolved in a solvent.
[0046] In one embodiment, a heat cycle test assuming a higher operating temperature (higher Tj) of the power semiconductor is performed at a temperature of 175°C or higher. Furthermore, mounting the semiconductor and reflow are performed at a high temperature of about 260°C. Therefore, in one embodiment, the Tg of the polyamide-imide resin is preferably 250°C or higher. The Tg of the polyamide-imide resin is more preferably 270°C or higher, even more preferably 290°C or higher, and even more preferably 300°C or higher.
[0047] Peeling between components during the reflow process when mounting a device occurs when the stress caused by the rapid evaporation of moisture contained in the device and the stress caused by the difference in linear expansion between the components exceed the adhesive force between the components. In one embodiment, from the viewpoint of suppressing peeling during the reflow process, the Tg of the polyamide-imide resin is preferably 300° C. or higher, and more preferably 320° C. or higher.
[0048] According to the polyamide-imide resin of the above embodiment, a Tg of 250° C. or more can be easily obtained. In the polyamide-imide resin of the above embodiment, the structural unit (Ia) is considered to contribute to an increase in Tg by having a skeleton known as a cardo structure. In addition, it is presumed that the presence of the structural units (IIa), (IIb) and (IIc) in the resin enables a further increase in Tg. In addition, when a film is formed using the polyamide-imide resin, the physical properties of the film, such as the CTE, elastic modulus, or adhesion to an adherend, tend to be easily adjustable. For example, by adjusting the compounding ratio of the structural unit (Ia) to the structural units (IIa), (IIb) and (IIc), the desired physical properties of the film, such as Tg, CTE, elastic modulus and adhesion, can be easily obtained. As a result, when the polyamide-imide resin of the above embodiment is used as a constituent material of a semiconductor device, it becomes easy to improve the reliability of the semiconductor device.
[0049] In general, the flexibility of a film made of a resin with a high Tg tends to be low. When the flexibility of the film is low, the stress generated in the semiconductor device cannot be relieved, and the film is likely to peel off. From this viewpoint, in one embodiment, the polyamide-imide resin preferably contains a structural unit (IIIa) represented by the following formula. It is considered that the flexibility of the polyamide-imide resin of the above embodiment is improved by further having the structural unit (IIIa), and thus a film having excellent flexibility can be easily obtained.
[0050] [ka]
[0051] In the structural unit (IIIa), each R independently represents a hydrogen atom or a substituent selected from the group consisting of an alkyl group having 1 to 9 carbon atoms, an alkoxy group having 1 to 9 carbon atoms, and a halogen atom. The halogen atom may be a fluorine atom, a chlorine atom, or a bromine atom. The alkyl group and the alkoxy group may have any of a straight-chain structure, a branched structure, and a cyclic structure. In one embodiment, each R is independently preferably an alkyl group having 1 to 9 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, and further preferably an alkyl group having 1 to 3 carbon atoms. n represents an integer of 1 to 6. n is preferably an integer of 2 to 4, and more preferably 3 or 4.
[0052] In one embodiment, the structural unit (IIIa) can be derived using a compound represented by the following formula (III): The structural unit (IIIa) corresponds to a residue obtained by removing the substituent Y (amino group or isocyanate group) from the compound represented by the following formula (III), and may be directly bonded to an amide bond site or an imide bond site in the resin structure. [ka]
[0053] In the above formula (III), Y is an amino group (-NH2) or an isocyanate group (-NCO), and R and n are as described above.
[0054] Specific examples of the compound represented by formula (III) above include 1,3-bis(3-aminopropyl)1,1,3,3-tetramethyldisiloxane, 1,3-bis(2-aminoethyl)1,1,3,3-tetramethyldisiloxane, 1,3-bis(aminomethyl)1,1,3,3-tetramethyldisiloxane, 1,3-bis(4-aminobutyl)1,1,3,3-tetramethyldisiloxane, 1,3-bis(5-aminopentyl)1,1,3,3-tetramethyldisiloxane, and 1,3-bis(6-aminohexyl)1,1,3,3-tetramethyldisiloxane.
[0055] As described above, the polyamideimide resin of the above embodiment is considered to be easily able to achieve both a high glass transition temperature (Tg) and flexibility of the resin by further having the structural unit (IIIa) in addition to the combination of the structural unit (Ia) and at least one selected from the group consisting of the structural units (IIa), (IIb) and (IIc). Therefore, for example, when a primer layer provided between each member of a semiconductor device contains the polyamideimide resin of the above embodiment, excellent adhesion can be easily obtained even in each test performed in a high temperature range of 250°C or more. In addition, when the constituent material of the power semiconductor device contains the polyamide-imide resin of the above embodiment, it is possible to suppress the resin from softening due to heat generation during operation, which leads to a decrease in adhesion. Therefore, the polyamide-imide resin of the above embodiment makes it possible to obtain high reliability in the power semiconductor device.
[0056] In the polyamideimide resin, the proportion of the structural unit (Ia) relative to the total amount of the structural units derived from the diamine component and / or the diisocyanate component may be 10 mol% or more, 15 mol% or more, 18 mol% or more, 30 mol% or more, 40 mol% or more, 45 mol% or more, 55 mol% or more, 65 mol% or more, or 70 mol% or more. The proportion of the structural unit (Ia) may be 95 mol% or less, 90 mol% or less, 85 mol% or less, 80 mol% or less, or 75 mol% or less. In one embodiment, the proportion of the structural unit (Ia) may be 10 to 95 mol%, preferably 15 to 95 mol%, more preferably 45 to 90 mol%, even more preferably 55 to 85 mol%, and still more preferably 65 to 80 mol%.
[0057] In one embodiment, the total amount of the structural unit (Ia) and at least one of the structural units (IIa), (IIb) and (IIc) derived from the diamine component and / or the diisocyanate component may be 70 mol% or more, 80 mol% or more, 85 mol% or more, 90 mol% or more, or 100 mol%. In one embodiment, the total amount may be 95 mol% or less. In one embodiment, based on the total amount of the structural unit (Ia) and at least one selected from the group consisting of the structural units (IIa), (IIb), and (IIc), the proportion of the structural unit (Ia) may be 20 mol% or more. The proportion of the structural unit (Ia) may be preferably 45 mol% or more, more preferably 50 mol% or more, even more preferably 80 mol% or more, and even more preferably 85 mol% or more.
[0058] On the other hand, the proportion of at least one of the structural units (IIa), (IIb) and (IIc) is preferably 10 mol% or more based on the total amount of the structural units derived from the diamine component and / or the diisocyanate component. In one embodiment, the above proportion may be preferably 10 to 80 mol%, more preferably 12 to 65 mol%, and even more preferably 15 to 50 mol%. Note that, when the polyamideimide resin contains two or more of the structural units (IIa), (IIb) and (IIc), the above proportion refers to the total proportion thereof.
[0059] In the polyamideimide resin, the total amount of the structural units (Ia) and at least one of (IIa), (IIb) and (IIc) is preferably 35 mol% or more, more preferably 40 mol% or more, and even more preferably 45 mol% or more, based on the total amount of all structural units constituting the resin. Here, the proportion (mol%) of each structural unit is calculated from the number of moles of the monomer compound corresponding to each structural unit.
[0060] In another embodiment, the polyamideimide resin preferably further comprises a structural unit (IIIa). In one embodiment, the proportion of the structural unit (IIIa) relative to the total amount of the structural units derived from the diamine component and / or the diisocyanate component may be 20 mol% or less, 15 mol% or less, or 10 mol% or less. The proportion of the structural unit (IIIa) may be 2.5 mol% or more, 5.0 mol% or more, or 7.5 mol% or more. In the above embodiment, as structural units derived from the diamine component and / or the diisocyanate component, the total amount of the proportion of the structural unit (Ia), the proportion of at least one of the structural units (IIa), (IIb), and (IIc), and the proportion of the structural unit (IIIa) may be 75 mol % or more, 80 mol % or more, 85 mol % or more, 90 mol % or more, 95 mol % or more, or 100 mol %. In the above embodiment, the proportion of the structural unit (IIIa) may be preferably 2.5 to 20 mol%, more preferably 5 to 15 mol%, and further preferably 7.5 to 10 mol%. By adjusting the proportion of the structural unit (IIIa) within the above range, the properties of the structural unit (Ia) and at least one of the structural units (IIa), (IIb), and (IIc) can be easily exhibited.
[0061] In still another embodiment, the polyamideimide resin may further contain, in addition to the structural unit (Ia), at least one selected from the group consisting of the structural units (IIa), (IIb) and (IIc), and, if necessary, the structural unit (IIIa), an additional structural unit other than these structural units. The additional structural units may be structural units derived from aromatic diamines or aromatic diisocyanates, aliphatic diamines or aliphatic diisocyanates, and alicyclic diamines or alicyclic diisocyanates, which have structures different from the structural units (Ia), (IIa), (IIb), (IIc), and (IIIa). The proportion of such additional structural units is preferably 20 mol% or less based on the total amount of structural units derived from the diamine component and / or diisocyanate component. The proportion of the additional structural units is more preferably 10 mol% or less, and even more preferably 5 mol% or less.
[0062] Examples of aromatic diamines (diisocyanates) from which additional structural units can be derived include: 2,7-diaminofluorene, 9,9-bis[4-(4-aminophenoxy)phenyl]-9H-fluorene, 2,2'-ditrifluoromethyl-4,4'-diaminobiphenyl, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 4,4'-diamino-2,2'-biphenyldisulfonic acid, 3,4'-diaminodiphenyl ether, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 2,2-bis(4-aminophenyl)hexafluoropropane, 1,4-phenylenediamine, 2-chloro-1,4-phenylenediamine, 1,3-phenylenediamine, 4,4'-diaminobenzophenone, 3,3'-diaminobenzophenone, 3,4'-diaminodiphenylmethane, 4,4'-diaminobenzanilide, 3,6-diaminocarbazole, 4,4'-bis(4-aminophenoxy)biphenyl, 2-trifluoromethyl-1,4-diaminobenzene, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis(4-aminophenyl)hexafluoropropane, 2,2'-bis(trifluoromethyl)benzidine, 2,2'-ditrifluoromethyl-4,4'-diaminobiphenyl ether, 4-aminophenyl sulfide, 4,4'-diamino-3,3'-dimethylbiphenyl, Naphthalenediamine, Naphthalene diisocyanate is an example.
[0063] Examples of aliphatic diamines (diisocyanates) from which additional structural units can be derived include: 1,4-cyclohexanediamine, 1,3-cyclohexanediamine, 1,4-di(aminomethyl)cyclohexane, 1,3-bis(aminomethyl)cyclohexane, bis(aminomethyl)norbornane, 4,4'-methylenebis(cyclohexylamine), hexamethylenediamine, Hexamethylene diisocyanate is an example.
[0064] In one embodiment, when a diamine is used in the production of a polyamide-imide resin, an anhydride of an aliphatic or aromatic tricarboxylic acid can be used. From the viewpoint of heat resistance, it is preferable to use an anhydride of an aromatic tricarboxylic acid. In one embodiment, for example, it is preferable to use an acid halide of trimellitic anhydride as an acid component. Among them, it is particularly preferable to use trimellitic anhydride chloride represented by the following formula (IV). [ka]
[0065] In view of the above, in one embodiment, the polyamideimide resin preferably contains a structural unit represented by the following formula (IVa) which can be derived from a reaction between an acid halide of trimellitic anhydride and a diamine component. [ka] In one embodiment, based on the total amount of the structural units derived from the acid component, the ratio of the structural units derived from the above formula (IV) is preferably 50 mol% or more, more preferably 75 mol% or more, and even more preferably 90 mol% or more. That is, based on the total mass of the acid component, in one embodiment, the content of the acid halide of trimellitic anhydride is preferably 50 mass% or more, more preferably 75 mass% or more, and even more preferably 90 mass% or more. In one embodiment, the ratio of the structural unit derived from the above formula (IV) to the total amount of the acid component may be 100 mol %. That is, in one embodiment, the content of the acid halide of trimellitic anhydride may be 100 mass % based on the total mass of the acid component.
[0066] In one embodiment, the polyamideimide resin may be a resin obtained by using a compound represented by the above formula (I) and at least one compound selected from the group consisting of the above formulas (IIA), (IIB) and (IIC) as a diamine component or diisocyanate component, and a compound represented by the above formula (IV) as an acid component. In another embodiment, the polyamideimide resin may be a resin obtained by further adding a compound represented by the above formula (III) as a diamine component or diisocyanate component. In yet another embodiment, the polyamideimide resin may be a resin obtained by further using an acid component other than the compound represented by the above formula (IV) as an acid component.
[0067] The acid component that can be used may include, for example, the above-mentioned tricarboxylic acid anhydrides other than the compound represented by the above formula (IV) or their acid halides, and tricarboxylic acids such as trimellitic acid. In addition, as the acid component, tetracarboxylic acid dianhydrides such as pyromellitic anhydride and biphenyltetracarboxylic acid dianhydride, aromatic dicarboxylic acids such as terephthalic acid and isophthalic acid, alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid, and aliphatic dicarboxylic acids such as adipic acid and sebacic acid may also be used.
[0068] The weight average molecular weight (Mw) of the polyamideimide resin is preferably in the range of 30,000 to 120,000. A polyamideimide resin having an Mw within the above range is likely to form a coating film of a preferred thickness, which will be described later, during coating. The Mw of the polyamideimide resin is more preferably in the range of 35,000 to 110,000, and even more preferably in the range of 38,000 to 100,000. The "Mw" described in this specification is a value measured using gel permeation chromatography in terms of standard polystyrene.
[0069] The polyamide-imide resin is preferably soluble in an organic solvent at room temperature from the viewpoint of workability during film formation. In this specification, "soluble in an organic solvent at room temperature" means that when an organic solvent is added to a resin and stirred at room temperature, the solution is visually observed to be transparent without any precipitate or turbidity. Here, the "room temperature" may be in the range of about 10°C to 40°C, and preferably in the range of 20°C to 30°C. In one embodiment, the "solution" means, for example, a solution obtained by adding 1 to 30 g of the powder of the resin to 100 mL of organic solvent. The organic solvent will be described later.
[0070] (Method of producing polyamide-imide resin) The polyamideimide resin can be produced according to a known method, and is not particularly limited. The polyamideimide resin can be produced, for example, through a reaction between a diamine component and / or a diisocyanate component and an acid component. The diamine component, the diisocyanate component, and the acid component are as described above. The reaction can be carried out without a solvent or in the presence of an organic solvent. The reaction temperature is preferably in the range of 25°C to 250°C. The reaction time can be appropriately adjusted depending on the batch scale, the reaction conditions employed, and the like.
[0071] The organic solvent (reaction solvent) used in the production of polyamideimide resin is not particularly limited. Examples of organic solvents that can be used include ether-based solvents such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, and triethylene glycol diethyl ether; sulfur-containing solvents such as dimethyl sulfoxide, diethyl sulfoxide, dimethyl sulfone, and sulfolane; cyclic ester-based (lactone-based) solvents such as γ-butyrolactone; non-cyclic ester-based solvents such as cellosolve acetate; ketone-based solvents such as cyclohexanone and methyl ethyl ketone; nitrogen-containing solvents such as N-methyl-2-pyrrolidone, dimethylacetamide, and 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidinone; and aromatic hydrocarbon-based solvents such as toluene and xylene. One of these organic solvents may be used alone, or two or more may be used in combination. In one embodiment, it is preferable to select and use an organic solvent capable of dissolving the resin to be produced, and it is preferable to use a polar solvent, which will be described later, for example, a nitrogen-containing solvent.
[0072] In one embodiment, the polyamideimide resin can be produced by a method in which a precursor of the polyamideimide resin is first produced by reacting an acid component with a diamine component, and then the precursor is dehydrated and cyclized to obtain a polyamideimide resin. However, the method for cyclizing the precursor is not particularly limited, and any method known in the art can be used. For example, a thermal cyclization method in which dehydration and cyclization are performed by heating under normal or reduced pressure, or a chemical cyclization method in which a dehydrating agent such as acetic anhydride is used in the presence or absence of a catalyst can be used.
[0073] In the case of the thermal ring-closing method, it is preferable to carry out the dehydration reaction while removing water generated from the system. During the dehydration reaction, the reaction liquid may be heated to 80° C. to 400° C., preferably 100° C. to 250° C. In addition, water may be removed azeotropically by using an organic solvent capable of forming an azeotrope with water, such as benzene, toluene, or xylene.
[0074] In the case of the chemical ring-closing method, the reaction may be carried out in the presence of a chemical dehydrating agent at 0° C. to 120° C., preferably 10° C. to 80° C. As the chemical dehydrating agent, for example, acid anhydrides such as acetic anhydride, propionic anhydride, butyric anhydride, and benzoic anhydride, and carbodiimide compounds such as dicyclohexylcarbodiimide, etc. are preferably used. During the reaction, it is preferable to use in combination a substance that promotes the cyclization reaction, such as pyridine, isoquinoline, trimethylamine, triethylamine, aminopyridine, and imidazole.
[0075] The chemical dehydrating agent may be used in an amount of 90 to 600 mol % based on the total amount of the diamine components, and the cyclization reaction promoting substance may be used in an amount of 40 to 300 mol % based on the total amount of the diamine components. In addition, dehydration catalysts such as triphenyl phosphite, tricyclohexyl phosphite, triphenyl phosphate, phosphoric acid, phosphorus compounds such as phosphorus pentoxide, boric acid, boric anhydride, and other boron compounds may be used.
[0076] In the production of polyamide-imide resin, the ratio (molar ratio) of the acid component and the diamine component (diisocyanate component) is not particularly limited and can be adjusted so that the reaction proceeds without excess or deficiency. In one embodiment, from the viewpoint of the molecular weight and crosslinking degree of the produced polyamide-imide resin, the total amount of the diamine components is preferably 0.90 to 1.10 mol, more preferably 0.95 to 1.05 mol, and even more preferably 0.97 to 1.03 mol per 1.00 mol of the total amount of the acid components.
[0077] <Polyamide-imide resin composition> In one embodiment, a polyamideimide resin composition (hereinafter sometimes abbreviated as a resin composition) contains the polyamideimide resin of the above embodiment and a solvent. In this specification, the resin composition may be referred to as a varnish. (solvent) The solvent is not particularly limited as long as it can dissolve the polyamide-imide resin. The term "solvent capable of dissolving the polyamide-imide resin" refers to a solvent that, without any particular limitation on the temperature of the solvent, does not show any precipitation or turbidity when the solution obtained by adding the polyamide-imide resin powder to the solvent and stirring it is visually observed, and the entire solution is transparent. In one embodiment, the solvent constituting the resin composition may be the same as the reaction solvent used in the production of the resin. In particular, it is preferable to use a polar solvent.
[0078] Examples of polar solvents include nitrogen-containing compounds such as N-methylpyrrolidone, dimethylacetamide, dimethylformamide, and 1,3-dimethyltetrahydro-2(1H)-pyrimidinone; sulfolane, dimethylsulfoxide, and other sulfur-containing compounds; lactones such as γ-butyrolactone, γ-valerolactone, γ-caprolactone, γ-heptalactone, α-acetyl-γ-butyrolactone, and ε-caprolactone; ketones such as methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, and acetophenone; acyclic esters such as cellosolve acetate; ethylene glycol, glycerin, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, and diethylene glycol dibutyl ether; triethylene glycol dimethyl ether, triethylene glycol diethyl ether. , triethylene glycol dialkyl ethers such as triethylene glycol dipropyl ether and triethylene glycol dibutyl ether, tetraethylene glycol dialkyl ethers such as tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol dipropyl ether and tetraethylene glycol dibutyl ether, diethylene glycol monoalkyl ethers such as diethylene glycol monomethyl ether and diethylene glycol monoethyl ether, triethylene glycol monoalkyl ethers such as triethylene glycol monomethyl ether and triethylene glycol monoethyl ether, and tetraethylene glycol monoalkyl ethers such as tetraethylene glycol monomethyl ether and tetraethylene glycol monoethyl ether.
[0079] In one embodiment, the solvent is preferably at least one selected from the group consisting of diethylene glycol dimethyl ether, triethylene glycol, triethylene glycol dimethyl ether, N-methyl-2-pyrrolidone, γ-butyrolactone, γ-valerolactone, δ-valerolactone, γ-caprolactone, ε-caprolactone, α-methyl-γ-butyrolactone, ethyl cellosolve, ethyl cellosolve acetate, butyl cellosolve, butyl cellosolve acetate, cyclopentanone, cyclohexanone, tetrahydrofuran, 1,4-dioxane, dibutyl ether, dimethyl sulfoxide, 1,3-dimethyl-2-imidazolidinone, dimethylacetamide, N,N-dimethylformamide, ethylene carbonate, propylene carbonate, and propylene glycol methyl acetate. When two or more types are used in combination, they can be mixed in any ratio.
[0080] Among the above solvents, solvents having a relatively low boiling point are preferred from the viewpoint of film-forming properties, such as diethylene glycol dimethyl ether, triethylene glycol, and triethylene glycol dimethyl ether.
[0081] The amount of the solvent in the resin composition can be appropriately adjusted in consideration of the viscosity. Although not particularly limited, in one embodiment, the amount of the solvent is preferably 500 to 3,500 parts by mass relative to 100 parts by mass of the total amount of the resin in the resin composition. More preferably, the solvent is mixed in a ratio of 5,000 to 2,000 parts by mass relative to 100 parts by mass of the total amount of the resin.
[0082] (Additives) If necessary, additives such as colorants and coupling agents, and additional components such as resin modifiers may be added to the polyamideimide resin composition (varnish). When the polyamideimide resin composition contains additional components, the amount of the additional components is preferably 50 parts by mass or less per 100 parts by mass of the total amount of polyamideimide resin (solid components) in the polyamideimide resin composition. By making the amount of the additional components 50 parts by mass or less, it becomes easy to suppress the deterioration of the physical properties of the resulting coating film.
[0083] In one embodiment, the polyamideimide resin composition may contain a coupling agent. Examples of usable additional components are given below. (Coupling Agent) The coupling agent that can be used is not particularly limited, and may be any of silane, titanium, and aluminum, but silane coupling agents are most preferred.The silane coupling agent is not particularly limited, and examples thereof include vinyl trichlorosilane, vinyl tris(β-methoxyethoxy)silane, vinyl triethoxysilane, vinyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-methacryloxypropyl methyl dimethoxysilane, β-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-glycidoxypropyl methyl dimethoxysilane, γ-glycidoxypropyl methyl diethoxysilane, N-β(aminoethyl) γ-aminopropyl trimethoxysilane, N-β(aminoethyl) γ-aminopropyl methyl dimethoxysilane, γ-aminopropyl triethoxysilane, N-phenyl-γ-aminopropyl trimethoxysilane, γ-mercapto ... tripropyltrimethoxysilane, gamma-mercaptopropyltriethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-ureidopropyltriethoxysilane, 3-ureidopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyl-tris[2-(2-methoxyethoxy)ethoxy]silane, N-methyl-3-aminopropyltrimethoxysilane, triaminopropyl-trimethoxysilane, 3-4,5-dihydroimidazol-1-yl-propyltrimethoxysilane, 3-methacryloxypropyl-trimethoxysilane, 3-mercaptopropyl-methyldimethoxysilane, 3-chloropropyl-methyldimethoxysilane, 3-chloropropyl-dimethoxysilane, 3-cyanopropyl-triethoxysilane, hexamethyldisilazane, N,O-bis(trimethylsilyl)acetamide, methyltrimethoxysilane, methyltriethoxysilane, ethyltrichlorosilane, n-propyltrimethoxysilane, isobutyltrimethoxysilane, amyltrichlorosilane, octyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, methyltri(methacryloyloxyethoxy)silane, methyltri(glycidyloxy)silane, N-β(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane, octadecyldimethyl[3-(trimethoxysilyl)propyl]ammonium chloride, γ-chloropropylmethyldichlorosilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropylmethyldiethoxysilane, trimethylsilyl isocyanate, dimethylsilyl isocyanate, methylsilyl triisocyanate, vinylsilyl triisocyanate, phenylsilyl triisocyanate, tetraisocyanate silane, and ethoxysilane isocyanate. These may be used alone or in combination of two or more.
[0084] The titanium-based coupling agent is not particularly limited, but examples thereof include isopropyl trioctanoyl titanate, isopropyl dimethacryl isostearoyl titanate, isopropyl tridodecylbenzenesulfonyl titanate, isopropyl isostearoyl diacryl titanate, isopropyl tri(dioctyl phosphate) titanate, isopropyl tricumyl phenyl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, isopropyl tris(n-aminoethyl) titanate, tetraisopropyl bis(dioctyl phosphite) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, tetra(2,2-diallyloxymethyl-1-butyl)bis(ditridecyl)phosphite titanate, dicumyl phenyloxyacetate titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, tetraisopropyl ... butyl titanate, butyl titanate dimer, tetra(2-ethylhexyl) titanate, titanium acetylacetonate, polytitanium aethylacetonate, titanium octylene glycolate, titanium lactate ammonium salt, titanium lactate, titanium lactate ethyl ester, titanium chile ethanol aminate, polyhydroxytitanium stearate, tetramethyl orthotitanate, tetraethyl orthotitanate, tetrapropyl orthotitanate, tetraisobutyl orthotitanate, stearyl titanate, cresyl titanate monomer, cresyl titanate polymer, diisopropoxy-bis(2,4-pentadionate)titanium(IV), diisopropyl-bis-triethanolamino titanate, octylene glycol titanate, tetra-n-butoxytitanium polymer, tri-n-butoxytitanium monostearate polymer, tri-n-butoxytitanium monostearate, and the like. These may be used alone or in combination of two or more.
[0085] The aluminum coupling agent is not particularly limited, but examples thereof include aluminum chelate compounds such as ethyl acetoacetate aluminum diisopropylate, aluminum tris(ethyl acetoacetate), alkyl acetoacetate aluminum diisopropylate, aluminum monoacetylacetate bis(ethyl acetoacetate), aluminum tris(acetylacetonate), aluminum monoisopropoxy monooleoxyethyl acetoacetate, aluminum di-n-butoxide mono-ethyl acetoacetate, and aluminum di-isopropoxide mono-ethyl acetoacetate, aluminum isopropylate, mono-sec-butoxy aluminum diisopropylate, aluminum sec-butylate, and aluminum ethylate. These may be used alone or in combination of two or more.
[0086] In one embodiment, the viscosity of the polyamideimide resin composition is preferably in the range of 10 mPa·s to 400 mPa·s, more preferably in the range of 10 mPa·s to 300 mPa·s. Here, the above viscosity is a value obtained by measuring a varnish dissolved in a solvent so that the non-volatile component (solid component) is 1 to 20 mass % at 25°C using an E-type viscometer at 10 rpm. If the viscosity measured at 10 rpm is 10 mPa·s or more, it is easy to ensure a sufficient film thickness when applied. Also, if the viscosity is 400 mPa·s or less, it is easy to ensure a uniform film thickness when applied. Therefore, by adjusting the viscosity within the above range, it is easy to obtain excellent printability.
[0087] In one embodiment, from the viewpoint of obtaining excellent applicability, the viscosity is preferably more than 50 mPa·s, and more preferably more than 100 mPa·s. If the viscosity is too low, the composition may be difficult to handle due to spreading beyond a predetermined range. The viscosity can be measured, for example, using a viscometer (RE type) manufactured by Toki Sangyo Co., Ltd. In the measurement, the measurement temperature is set to 25°C ± 0.5°C, and then 1 mL to 1.5 mL of the resin composition (varnish) is placed in the viscometer, and the viscosity is recorded 10 minutes after the start of the measurement.
[0088] In one embodiment, the thickness of the film formed from the resin composition is not particularly limited, but may be in the range of 0.5 to 50 μm. By having a thickness within the above range, sufficient adhesion tends to be easily ensured. From the above viewpoint, the film thickness is preferably in the range of 1 to 15 μm, and more preferably in the range of 3 to 15 μm.
[0089] In one embodiment, the elastic modulus at 35°C of a film having a thickness of 10 μm obtained by applying and drying the resin composition (varnish) by heating is preferably in the range of 0.5 GPa to 8.0 GPa, more preferably in the range of 1.0 GPa to 5.0 GPa, and even more preferably in the range of 2.0 GPa to 4.5 GPa. The heat drying for forming the film can be performed under conditions of, for example, heating at 50°C for 10 minutes and then drying at 260°C for 1 hour. The elastic modulus is a value measured using a dynamic viscoelasticity measuring device. From the viewpoint of further increasing the reliability of the power semiconductor device, it is preferable that the film has appropriate flexibility. Therefore, in one embodiment, the elastic modulus of the film is more preferably in the range of 3.0 GPa to 4.5 GPa.
[0090] The elastic modulus can be measured, for example, using a dynamic viscoelasticity measuring device "Rheogel-E4000 type" manufactured by UBM Co., Ltd. The elastic modulus is a value obtained by measuring, for example, a film obtained by applying and drying a resin composition (varnish) under conditions of a measurement frequency of 10 MHz and a measurement temperature of 35°C.
[0091] The resin composition of the above embodiment has excellent heat resistance and flexibility, and therefore can be suitably used as a constituent material of a semiconductor device. For example, the resin composition can be used to form an insulating layer, an adhesive layer, a protective layer, etc. in a semiconductor device, and the semiconductor device having these layers has excellent adhesion between each member and excellent reliability. In one embodiment, the resin composition can be suitably used to form a primer layer provided between an encapsulant and a substrate, or between an encapsulant and a semiconductor element in a semiconductor device. The adhesion between each member can be evaluated by shear strength.
[0092] In one embodiment, the shear strength between members having a primer layer made of the resin composition at 260° C. is preferably 11 MPa or more, more preferably 15 MPa or more, and even more preferably 17 MPa or more. If the shear strength at 260° C. is 11 MPa or more, it is easy to obtain excellent adhesion even when the resin composition is applied to a power semiconductor device.
[0093] In one embodiment, in a laminate having a primer layer and a resin sealing layer, which are formed of the resin composition, on a substrate, the shear strength between the substrate and the resin sealing layer can be 11 MPa or more at 260° C. The laminate can be obtained by applying a resin composition (varnish) onto a substrate and drying the same to form a film, and then forming a resin sealing layer thereon.
[0094] The shear strength can be measured, for example, using a shear strength measuring device (4000 series manufactured by Nordson Advanced Technology Co., Ltd.). In the measurement, for example, a sample can be used in which a resin composition is applied and dried on a Ni substrate to form a film, and a resin sealing layer of φ5 mm is molded thereon using an epoxy-based sealing resin. The conditions during measurement may typically be a heat stage temperature of 260° C. and a probe speed of 3 mm / min. The material of the substrate and the sealing material constituting the resin sealing layer can also be changed as appropriate. In the measurement, a Cu substrate may be used instead of the Ni substrate, or a Cu substrate plated with Ag may be used.
[0095] As described above, when the resin composition is used to form a primer layer provided between an encapsulant and a substrate, or between an encapsulant and a semiconductor element, etc., in a semiconductor device, it is preferable that the difference in the coefficient of linear expansion (CTE) between each member and a film made of the resin composition is small from the viewpoint of suppressing the generation of stress due to thermal expansion and contraction and improving adhesion. From this viewpoint, in one embodiment, the coefficient of linear expansion (CTE) of the polyamideimide resin is preferably in the range of 40 to 90 ppm / °C, more preferably in the range of 50 to 70 ppm / °C, and even more preferably in the range of 55 to 65 ppm / °C. In addition, the CTE of the resin composition containing the polyamideimide resin is also preferably within the above range.
[0096] The CTE is a value measured using a film obtained by applying and drying a varnish of a resin or a resin composition. For the measurement, for example, a thermomechanical analyzer (TMA, Hitachi High-Tech Science Corporation "SS7100") can be used. The measurement conditions can be a chuck distance of 10 mm, a load of 10 g, and a heating rate of 10°C / min. The CTE specified in this specification is a value calculated from the slope of a straight line connecting the values at 70°C and 140°C.
[0097] <Semiconductor device> One embodiment relates to a semiconductor device having a substrate and a dry film formed using the resin composition of the embodiment. The components of the semiconductor device generally include a semiconductor element mounted on a substrate and a sealing member (sealing layer). The semiconductor element is typically made of inorganic materials such as semiconductor chips (Si, SiC, GaN), Cu, Ni plating, Ag plating, Au plating, Au / Pd / Ni plating, solder, sintered silver, sintered copper, Al wire, Au wire, and ceramic substrates (alumina, alumina zirconia, aluminum nitride, silicon nitride). The sealing layer is typically made of organic materials such as resin. Hereinafter, the sealing layer made of resin is referred to as a resin sealing layer.
[0098] In the semiconductor device, the adhesion between the components can be easily improved by forming a dry film using the resin composition of the embodiment as a primer layer between each component. More specifically, for example, by forming a dry film of the resin composition between the resin sealing layer and the substrate, or between the resin sealing layer and the semiconductor element, the adhesion between each component can be ensured, and peeling during cycle testing can be prevented. From this viewpoint, in one embodiment, the semiconductor device has a substrate, a semiconductor element mounted on the substrate, a primer layer provided on at least the semiconductor element mounting surface of the substrate, and a resin sealing layer provided on the primer layer, and the primer layer is preferably composed of a dry film formed using the resin composition for semiconductor device of the embodiment. The substrate may be a lead frame composed of a die pad on which a semiconductor element is mounted and a lead, and the electrode pad of the semiconductor element and the lead of the lead frame are electrically connected via a wire.
[0099] In one embodiment, the resin composition can be suitably used as a constituent material of a power semiconductor device using the silicon carbide (SiC) substrate or the gallium nitride (GaN) substrate. When the resin composition is used to constitute a power semiconductor device, a decrease in adhesion between the components during a heat cycle test can be easily suppressed.
[0100] A typical structure of the semiconductor device of the above embodiment will be specifically described below with reference to the drawings. FIG. 1 is a schematic cross-sectional view showing one embodiment of a semiconductor device. The semiconductor device shown in FIG. 1 has a die pad 1a, a semiconductor element 2, a primer layer 3, leads 1b, wires 4, and a resin sealing layer 5, and the primer layer 3 is formed from the resin composition of the above embodiment. As shown in FIG. 1, the primer layer 3 formed from the resin composition is provided on the semiconductor element mounting surface (the surface of the lead 1b and the die pad 1a on which the semiconductor element 2 is mounted) of the substrate 1 that contacts the resin sealing layer 5, and thus the adhesion between each member can be easily improved.
[0101] In one embodiment, a method for manufacturing a semiconductor device includes at least a step of applying the resin composition of the above embodiment to a surface of a substrate carrying a semiconductor element and drying the resin composition to form a primer layer, and a step of forming a resin sealing layer on the primer layer.
[0102] In the above embodiment, the primer layer is formed using the resin composition of the above embodiment. From the viewpoint of workability, it is preferable to use a resin composition (varnish) containing a polyamideimide resin as a resin component. The primer layer can be obtained by applying the resin composition to a predetermined location and drying the coating.
[0103] The material of the lead frame, which is composed of a die pad on which a semiconductor element is mounted and a lead, is not particularly limited and can be selected from materials well known in the art. From the viewpoint of application to a power semiconductor device, the die pad material is preferably at least one selected from the group consisting of Ni and Cu. The one selected from the group consisting of Ni and Cu may have Ag plating on its surface. The lead material of the lead frame is preferably selected from the group consisting of Ni and Cu. The material of the semiconductor element is not particularly limited, and may be, for example, a silicon wafer, a silicon carbide wafer, or the like.
[0104] The resin sealing layer may be formed using a sealing material known in the art. For example, the resin sealing material may be a liquid or solid epoxy-based resin composition. The resin sealing layer may be formed by transfer molding using the resin sealing material. In another embodiment, the method for manufacturing a semiconductor device includes, for example, a step of applying and drying the resin composition of the above embodiment to a semiconductor substrate on which a plurality of wirings of the same structure are formed to form a resin layer, and a step of forming rewiring on the resin layer, which is electrically connected to the electrodes on the semiconductor substrate, as necessary. In addition to the above steps, the method may include a step of forming a protective layer (resin layer) on the rewiring or the resin layer using the resin composition of the above embodiment as necessary. Furthermore, in addition to the above steps, the method may include a step of forming an external electrode terminal on the resin layer as necessary, and then a step of dicing as necessary.
[0105] The method of applying the resin layer (primer layer) is not particularly limited, but is preferably spin coating, spray coating, or dispense coating. The method of drying the resin layer can be performed by a method known in the art. The resin composition of the above embodiment is also excellent in properties such as sputtering resistance, plating resistance, and alkali resistance required in the process of forming rewiring. Therefore, the resin composition of the above embodiment can be suitably used as a material for any semiconductor device without being limited to the configuration of the semiconductor device described above. EXAMPLES
[0106] The present invention will be described in detail below with reference to examples. However, the present invention is not limited to the following examples and includes various embodiments.
[0107] <1> Synthesis of polyamide-imide resin (Synthesis Example 1) 25.1 g of 9,9-bis(4-aminophenyl)fluorene, 3.6 g of 4,4'-diaminodiphenylmethane, and 2.5 g of 1,3-bis(3-aminopropyl)1,1,3,3-tetramethyldisiloxane were placed in a 1-liter four-neck flask equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a cooling tube equipped with an oil-water separator under a nitrogen stream, and 284 g of N-methyl-2-pyrrolidone (hereinafter referred to as NMP) was added and dissolved to obtain a solution. Next, 21.1 g of trimellitic anhydride chloride (hereinafter referred to as TAC) was added to the above solution while cooling so as not to exceed 20° C. After stirring at room temperature for 2 hours, 12.1 g of triethylamine (hereinafter referred to as TEA) was added and reacted at room temperature for at least 12 hours to obtain a polyamic acid solution. The obtained polyamic acid solution was further subjected to dehydration condensation at 180°C for 8 hours to obtain a polyamideimide resin solution. This polyamideimide resin solution was poured into water, and the obtained precipitate was separated, crushed, and dried to obtain a powdered polyamideimide resin (PAI-1). The obtained polyamideimide resin powder (PAI-1) was soluble in a polar solvent (NMP) at room temperature (25°C). The weight average molecular weight (Mw) of the obtained polyamideimide resin (PAI-1) was measured using gel permeation chromatography (hereinafter referred to as GPC) in terms of standard polystyrene, and was found to be 57,000 to 68,000.
[0108] The GPC measurement conditions are as follows. Liquid delivery pump: Shimadzu Corporation LC-20AD UV-Vis detector: Shimadzu Corporation SPD-20A, UV 270 nm Eluent: Tetrahydrofuran / dimethylformamide = 1 / 1 (volume ratio) + phosphoric acid 0.06M + lithium bromide 0.06M Column: Hitachi High-Technologies Corporation Gel Pack GL-S300MDT-5 x 2 Column size: 8mm l.D x 300mm Sample concentration: 5mg / 1mL Flow rate: 1 mL / min Column temperature: 40°C Molecular weight standards: Standard polystyrene
[0109] (Synthesis Example 2) A powdered polyamideimide resin (PAI-2) was obtained in the same manner as in Synthesis Example 1, except that in the preparation of the polyamideimide resin (PAI-1) described in Synthesis Example 1, the amount of 9,9-bis(4-aminophenyl)fluorene was changed to 15.7 g and the amount of 4,4'-diaminodiphenylmethane was changed to 8.9 g. The polyamideimide resin powder (PAI-2) was soluble in a polar solvent (NMP) at room temperature (25°C). The weight average molecular weight (Mw) of the obtained polyamideimide resin (PAI-2) was measured in terms of standard polystyrene and found to be 72,000. The Mw was measured in the same manner as in Synthesis Example 1.
[0110] (Synthesis Example 3) A powdered polyamideimide resin (PAI-3) was obtained in the same manner as in Synthesis Example 1, except that in the preparation of the polyamideimide resin (PAI-1) described in Synthesis Example 1, the amount of 9,9-bis(4-aminophenyl)fluorene was changed to 6.3 g and the amount of 4,4'-diaminodiphenylmethane was changed to 14.3 g. The polyamideimide resin powder (PAI-3) was soluble in a polar solvent (NMP) at room temperature (25° C.). The weight average molecular weight (Mw) of the obtained polyamideimide resin (PAI-3) was measured in terms of standard polystyrene and found to be 100,000. The Mw was measured in the same manner as in Synthesis Example 1.
[0111] (Synthesis Example 4) In a 1-liter four-neck flask equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a cooling tube equipped with an oil-water separator, 15.7 g of 9,9-bis(4-amino-3-methylphenyl)fluorene, 7.1 g of 1,5'-diaminonaphthalene, and 2.5 g of 1,3-bis(3-aminopropyl)1,1,3,3-tetramethyldisiloxane were placed under a nitrogen stream, and 250 g of NMP was added and dissolved to obtain a solution. Next, 21.1 g of TAC was added to the above solution while cooling it so that the temperature did not exceed 20° C. After stirring at room temperature for 2 hours, 12.1 g of TEA was added and reacted at room temperature for at least 12 hours to produce a polyamic acid solution. The obtained polyamic acid solution was further subjected to dehydration condensation at 180°C for 8 hours to obtain a polyamideimide resin solution. This polyamideimide resin solution was poured into water, and the obtained precipitate was separated, crushed, and dried to obtain a powdered polyamideimide resin (PAI-5). The polyamideimide resin powder (PAI-5) was soluble in a polar solvent (NMP) at room temperature (25°C). The weight average molecular weight (Mw) of the obtained polyamideimide resin (PAI-5) was measured using GPC in terms of standard polystyrene and found to be 65,000. The Mw was measured in the same manner as in Synthesis Example 1.
[0112] (Synthesis Example 5) In a 1-liter four-neck flask fitted with a thermometer, a stirrer, a nitrogen inlet tube, and a cooling tube equipped with an oil-water separator, 15.7 g of 9,9-bis(4-amino-3-methylphenyl)fluorene, 4.9 g of 1,4-phenylenediamine, and 2.5 g of 1,3-bis(3-aminopropyl)1,1,3,3-tetramethyldisiloxane were placed under a nitrogen stream, and 238 g of NMP was added and dissolved to obtain a solution. Next, 21.1 g of TAC was added to the above solution while cooling it so that the temperature did not exceed 20° C. After stirring at room temperature for 2 hours, 12.1 g of TEA was added and reacted at room temperature for at least 12 hours to produce a polyamic acid solution. The obtained polyamic acid solution was further subjected to dehydration condensation at 180°C for 8 hours to obtain a polyamideimide resin solution. This polyamideimide resin solution was poured into water, and the obtained precipitate was separated, crushed, and dried to obtain a powdered polyamideimide resin (PAI-5). The polyamideimide resin powder (PAI-5) was soluble in a polar solvent (NMP) at room temperature (25°C). The weight average molecular weight (Mw) of the obtained polyamideimide resin (PAI-5) was measured using GPC in terms of standard polystyrene and found to be 42,000. The Mw was measured in the same manner as in Synthesis Example 1.
[0113] (Synthesis Example 6) In a 1-L four-neck flask fitted with a thermometer, a stirrer, a nitrogen inlet tube, and a cooling tube equipped with an oil-water separator, 102.4 g of 2,2-bis[4-(4-aminophenoxy)phenyl]propane and 6.9 g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane were placed under a nitrogen stream, and 700 g of NMP was added and dissolved to obtain a solution. Next, 59.0 g of TAC was added to the above solution while cooling the reaction solution so that it did not exceed 20° C. After stirring at room temperature for 1 hour, 34.0 g of TEA was added while cooling the reaction solution so that it did not exceed 20° C., and the mixture was reacted at room temperature for 3 hours to produce a polyamic acid solution. The resulting polyamic acid solution was further subjected to dehydration condensation at 190° C. for 6 hours to produce a polyamideimide resin solution. The polyamideimide resin varnish was poured into water, and the resulting precipitate was separated, crushed, and dried to obtain a powdered polyamideimide resin (PAI-6). The weight average molecular weight (Mw) of the obtained polyamideimide resin (PAI-6) was measured using gel permeation chromatography (GPC) in terms of standard polystyrene, and was found to be 75,000. The Mw was measured in the same manner as in Synthesis Example 1.
[0114] <2> Preparation of polyamide-imide resin composition In the following Examples and Comparative Examples, polyamideimide resin compositions (primer varnish for semiconductor device) were prepared using the polyamideimide resin powders (PAI-1) to (PAI-6) prepared in the above Synthesis Examples 1 to 6, respectively.
[0115] Example 1 In a 0.5-liter four-neck flask, 12 g of the polyamideimide resin powder (PAI-1) obtained in Synthesis Example 1, 60.9 g of N-methyl-2-pyrrolidone, 26.1 g of butyl cellosolve acetate, and 1.2 g of a silane coupling agent (product name KBM-402 (3-glycidoxypropylmethyldimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd.) were added under a nitrogen gas flow, and the mixture was stirred for 12 hours to obtain a yellow reaction mixture. The obtained yellow reaction mixture was filled into a filter KST-47 (manufactured by Advantec Co., Ltd.) and filtered under pressure at a pressure of 0.3 MPa to obtain a primer varnish (P-1) for semiconductor device.
[0116] Example 2 A primer varnish for semiconductor device (P-2) was prepared in the same manner as in Example 1, except that the polyamideimide resin powder (PAI-1) used in Example 1 was changed to (PAI-2) obtained in Synthesis Example 2.
[0117] Example 3 A primer varnish for semiconductor device (P-3) was prepared in the same manner as in Example 1, except that the polyamideimide resin powder (PAI-1) used in Example 1 was changed to (PAI-3) obtained in Synthesis Example 3.
[0118] Example 4 A primer varnish for semiconductor device (P-4) was prepared in the same manner as in Example 1, except that the polyamideimide resin powder (PAI-1) used in Example 1 was changed to the powder (PAI-4) obtained in Synthesis Example 4.
[0119] Example 5 A primer varnish for semiconductor device (P-5) was prepared in the same manner as in Example 1, except that the polyamideimide resin powder (PAI-1) used in Example 1 was changed to the powder (PAI-5) obtained in Synthesis Example 5.
[0120] Comparative Example 1 A primer varnish for semiconductor device (P-6) was prepared in the same manner as in Example 1, except that the polyamideimide resin powder (PAI-1) used in Example 1 was changed to (PAI-6) obtained in Synthesis Example 6, and the solvent was changed to 35 g of N-methyl-2-pyrrolidone and 52 g of butyl cellosolve acetate.
[0121] <3> Evaluation of polyamide-imide resin composition (primer varnish for semiconductor device) Various characteristics were evaluated according to the following: (Elasticity Modulus) The primer varnishes (P-1) to (P-6) for semiconductor devices obtained in Examples 1 to 5 and Comparative Example 1 were applied to a substrate using a bar coater and dried by heating to obtain a dried film having a thickness of 10 μm. The drying by heating to form the dried film was carried out under the conditions of heating at 50° C. for 10 minutes, followed by drying at 260° C. for 1 hour. The dry film obtained as described above was used as a measurement sample, and the following measurements were carried out. The measurement sample was placed in a dynamic viscoelasticity measuring device (Rheogel-E4000) manufactured by UBM Co., Ltd., and the elastic modulus of the polyamide-imide resin was measured. The elastic modulus was measured at a chuck distance of 20 mm, a temperature of 35°C, and a measurement frequency of 10 MHz. The measured values are shown in Table 1.
[0122] (glass transition temperature) The primer varnishes (P-1) to (P-6) for semiconductor devices obtained in Examples 1 to 5 and Comparative Example 1 were applied to a substrate using a bar coater and dried by heating to obtain a dried film having a thickness of 10 μm. The drying by heating to form the dried film was carried out under the conditions of heating at 50° C. for 10 minutes, followed by drying at 260° C. for 1 hour. The dried film obtained as described above was used as a measurement sample, and the following measurements were performed. The measurements were performed using a thermomechanical analyzer (TMA, Hitachi High-Tech Science Corporation "SS7100") under the conditions of a chuck distance of 10 mm, a load of 10 g, and a heating rate of 10°C / min. The inflection point from α1 to α2 in the linear expansion coefficient obtained by the TMA measurement was taken as the glass transition temperature.
[0123] (Linear expansion coefficient) The primer varnishes for semiconductor device (P-1) to (P-6) obtained in Examples 1 to 5 and Comparative Example 1 were applied to a substrate using a bar coater and dried by heating to obtain a dried film having a thickness of 10 μm. To form the dried film, the substrate was heated at 50° C. for 10 minutes and then dried at 260° C. for 1 hour. The dry film obtained as described above was used as a measurement sample to measure the coefficient of linear expansion (CTE). The measurement was performed using a thermomechanical analyzer (TMA, Hitachi High-Tech Science Corporation "SS7100") under the conditions of a chuck distance of 10 mm, a load of 10 g, and a heating rate of 10 ° C. / min. The displacements at 70 ° C. and 140 ° C. were connected by a straight line, and the value calculated from the slope was taken as the CTE value.
[0124] (Adhesion (Shear strength)) The primer varnishes for semiconductor device (P-1) to (P-6) obtained in Examples 1 to 5 and Comparative Example 1 were evaluated for adhesion using a 4000 series shear strength measuring device manufactured by Arctec Corporation. Specifically, the primer varnish was first applied to a Ni substrate using a spray coating device (model number: SV91) manufactured by Sanei Tech Co., Ltd., and then dried by heating to obtain a dry film. The thickness of the dry film was 10 μm. Next, a resin sealing layer with a diameter of 5 mm was molded on the above-mentioned dried film to obtain a measurement sample. As the sealing material, an epoxy-based sealing resin (CEL-420HFC) manufactured by Showa Denko Materials Co., Ltd. was used. The obtained measurement sample was set on the heat stage of a 4000 series shear strength measuring device manufactured by Arctec Co., Ltd., and the shear strength was measured. The measurement was performed at a temperature of 260° C. and a probe speed of 3 mm / min. The results are shown in Table 1.
[0125] The adhesion in the high temperature range was evaluated according to the following criteria based on the results of the shear strength measurement at 260° C. The evaluation results are shown in Table 1. <Adhesion standards in high temperature ranges> A: The shear strength at 260℃ is 18.0MPa or more. B: The shear strength at 260°C is 11 MPa or more and less than 18.0 MPa. C: The shear strength at 260°C is less than 11 MPa.
[0126] (Reliability evaluation (moisture absorption reflow test)) For the primer varnishes for semiconductor device (P-1) to (P-6) obtained in Examples 1 to 5 and Comparative Example 1, a moisture absorption reflow test was carried out. Specifically, first, a package with a Si chip mounted on a Cu lead frame was assembled, and then the primer varnish was applied and dried to obtain a dried film using a spray coating device (model number: SV91) manufactured by Sanei Tech Co., Ltd. The drying conditions were a temperature of 260°C and a drying time of 1 hour. Next, a resin sealing layer was formed on the above-mentioned dried film using a sealing material (product name: "CEL-8240" manufactured by Showa Denko Materials Co., Ltd.) to obtain a sample for evaluation. Next, using the obtained evaluation samples, a moisture absorption reflow test was carried out under the following conditions. Moisture absorption conditions: JEDEC MSL 1 (85℃ / 85%RH x 168 hours), Reflow conditions: 260℃ / 10 seconds x 3 times
[0127] Next, the semiconductor devices before and after the reliability test (moisture absorption reflow test) were observed with a high-precision ultrasonic microscope (C-SAM) to check whether peeling occurred between the resin sealing layer, the resin dry film (primer layer), and the lead frame. The results are shown in Table 1. The evaluation results of the reliability test shown in Table 1 are shown as the number of samples in which peeling was confirmed (numerator) relative to the total number of samples evaluated (denominator). The observation conditions were as follows: Equipment: High-precision ultrasonic microscope (C-SAM), Sonoscan D9600, frequency 30MHz Conditions: Room temperature (25℃±5℃), pure water used.
[0128] The results of the evaluation of each characteristic in Examples 1 to 5 and Comparative Example 1 are summarized in Table 1. [Table 1]
[0129] In Table 1, the diamine-derived structural units I'-II' are structural units derived from 2,2-bis[4-(4-aminophenoxy)phenyl]propane.
[0130] As described above, the resin compositions of the present invention (Examples 1 to 5) were able to obtain excellent adhesion even under high temperature conditions of 260° C. On the other hand, the resin composition of Comparative Example 1 had a lower Tg than Examples 1 to 5, and showed significantly poor results in the adhesion test under high temperature conditions of 260° C. The resin composition of Comparative Example 1 uses a polyamideimide resin that does not have a cardo structure-type fluorene skeleton. In addition, it is understood from the results of the reliability test by the moisture absorption reflow test of Examples 1 to 3 that Tg can be easily increased by adjusting the ratio of the structural unit (Ia) and the structural unit (IIa). Furthermore, as seen in Examples 1, 4 and 5, when Tg exceeds 300°C, it is understood that not only excellent adhesion under high temperature conditions but also good results are obtained in the moisture absorption reflow test, and it is easy to improve reliability. From the above, it can be seen that according to the present invention, by having a polyamide-imide resin that has a combination of a structural unit having a cardo structure-type fluorene skeleton and a specific structural unit, it is possible to provide a resin and a resin composition that have excellent adhesion in high temperature regions and can improve the reliability of semiconductor devices. [Explanation of symbols]
[0131] 1 Lead frame, Cu substrate 1a Die Pad 1b Lead 2. Semiconductor elements 3 Primer layer (film of resin composition) 4 Wire 5 Resin sealing layer
Claims
1. A polyamideimide resin comprising a structural unit (Ia) represented by the following formula, and at least one selected from the group consisting of structural units (IIa), (IIb), and (IIc) represented by the following formulas: 【Chemistry 1】 [In formula (Ia), each X independently represents a hydrogen atom or a substituent selected from the group consisting of a halogen atom, an alkyl group having 1 to 9 carbon atoms, an alkoxy group having 1 to 9 carbon atoms, and a hydroxyalkyl group.] 【Chemistry 2】 [In formulas (IIa), (IIb), and (IIc), each S independently represents an alkyl group having 1 to 3 carbon atoms, a represents an integer of 0 to 4, b represents an integer of 0 to 3, and c represents an integer of 0 to 4.]
2. The polyamideimide resin according to claim 1, further comprising a structural unit (IIIa) represented by the following formula: 【Chemistry 3】 [In formula (IIIa), R each independently represents a hydrogen atom or a substituent selected from the group consisting of an alkyl group having 1 to 9 carbon atoms, an alkoxy group having 1 to 9 carbon atoms, and a halogen atom, and n represents an integer of 1 to 6.]
3. The polyamideimide resin according to claim 1 or 2, having a linear expansion coefficient of 40 to 70 ppm / °C.
4. The polyamideimide resin according to any one of claims 1 to 3, wherein the proportion of the structural unit (Ia) is 20 mol % or more based on the total amount of the structural unit (Ia) and the at least one selected from the group consisting of the structural units (IIa), (IIb), and (IIc).
5. The polyamideimide resin according to any one of claims 1 to 4, having a glass transition temperature of 250°C or higher.
6. The polyamideimide resin according to any one of claims 1 to 5, having a glass transition temperature of 300°C or higher.
7. A polyamideimide resin composition comprising the polyamideimide resin according to any one of claims 1 to 6 and a solvent.
8. A semiconductor device comprising a substrate and a film formed using the polyamideimide resin composition according to claim 7.
9. The semiconductor device according to claim 8 , further comprising a resin sealing layer.
Citation Information
Patent Citations
Polyamide-imide resin and optical element made therefrom
JP2000143802A
Method for producing polyamide-imide, and polyamide-imide and polyamide-imide varnish obtained thereby
JP2005146118A
Polyimide resin, heat-resistant resin laminated film using the same and metal layer-attached laminated film
JP2007077308A
Polyimide, polyamide imide, and film comprising the same
JP2008074991A
Polyimide precursor resin composition
JP2020007531A